2013
DOI: 10.5551/jat.13862
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin-Incorporated Nanoparticle-Eluting Stents Attenuate In-Stent Stenosis without Delayed Endothelial Healing Effects in a Porcine Coronary Artery Model

Abstract: Aim:The use of currently marketed drug-eluting stents presents safety concerns including increased late thrombosis, which is thought to result mainly from delayed endothelial healing effects (impaired re-endothelialization resulting in abnormal inflammation and fibrin deposition). We recently developed a bioabsorbable polymeric nanoparticle (NP)-eluting stent using a novel cationic electrodeposition technology. Statins are known to inhibit the proliferation of vascular smooth muscle cells (VSMC) and to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies. [18][19][20][21] Therefore, in the present study, we used a mouse model of post-infarct LV remodeling and tested the hypothesis that 1) PLGA nanoparticles are selectively delivered to inflammatory cells (mainly activated monocytes) and 2) the nanoparticlemediated targeting of pitavastatin to these inflammatory cells after establishment of MI protects the heart from LV remodeling by inhibiting recruitment of inflammatory monocytes to the infarcted heart.…”
Section: Editorial P472mentioning
confidence: 99%
See 1 more Smart Citation
“…Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies. [18][19][20][21] Therefore, in the present study, we used a mouse model of post-infarct LV remodeling and tested the hypothesis that 1) PLGA nanoparticles are selectively delivered to inflammatory cells (mainly activated monocytes) and 2) the nanoparticlemediated targeting of pitavastatin to these inflammatory cells after establishment of MI protects the heart from LV remodeling by inhibiting recruitment of inflammatory monocytes to the infarcted heart.…”
Section: Editorial P472mentioning
confidence: 99%
“…[14][15][16][17] We recently reported that nanoparticle-mediated delivery of pitavastatin showed significant therapeutic effects on pulmonary arterial hypertension, 18) restenosis, 19) ischemia-reperfusion injury, 20) and atherosclerosis 21) in animals by inhibiting the MCP1-CCR2 pathway. Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies.…”
Section: Editorial P472mentioning
confidence: 99%
“…By coating stents with PLGA-NPs containing anti-proliferative or anti-inflammatory drugs, these stents can be used to prevent restenosis after vascular intervention. We have reported a novel method to coat metal stents electrically and demonstrated the in vivo efficacy of stents coated with nanoparticles incorporated with imatinib mesylate, a tyrosine kinase inhibitor of PDGF receptor (ImatinibNPs), or Pitava-NPs 46,47) . After implantation of these stents in injured vasculatures, drugs coated on the stents surface are released and delivered to the surrounding vascular walls.…”
Section: Nanotechnology-based Drug Deliverymentioning
confidence: 99%
“…Possible application of nano-DDS in other cardiovascular diseases may include pulmonary hypertension, 12,17) vein graft disease, 53) and therapeutic neovascularization for clinical limb ischemia 15,18,54) and coronary stents. 14,19) We have started a phase I/IIa investigator initiated clinical trial in Kyushu University Hospital to test the efficacy of PLGA nanoparticle-mediated delivery of pitavastatin in patients with critical limb ischemia (UMIN000008011). Future clinical trials conducted in the next decade may prove the safety and efficacy of nano-DDS for cardiovascular diseases.…”
Section: Summary and Clinical Perspectivementioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] Dendrimers are highly branched macromole-cules with a controlled near monodisperse three-dimensional architecture emanating from a central core. Polymer growth starts from a central core molecule and growth occurs in an outward direction by a series of polymerization reactions, which determines the size of dendrimers starting from a few nanometers.…”
mentioning
confidence: 99%